Diversity of Crops and Land Use Pattern in Barisal Region - Ibrahim, M; Zaman, MAU; Mostafizur, ABM; Shahidullah, SM (Bangladesh Rice Journal, 2018)
Development workers, researchers and extensionists always need a comprehensive understanding and a reliable database on existing cropping patterns, cropping intensity and crop diversity of a particular area for the planning of future research and development. With this view, a survey-work was implemented over all the upazilas of Barisal region during 2016. A pre-tested semi-structured questionnaire was used as tool to document the existing cropping patterns, cropping intensity and crop diversity of the area. In the current investigation, 103 cropping patterns were identified. The highest number of cropping patterns 40 was found in Burhanuddin upazila of Bhola district and the lowest eight was in Betagi and Taltali of Barguna. The most dominant cropping pattern single T. Aman occupied 13.40% of net cropped area (NCA) of the region with its distribution over 33 upazilas out of 42. The second largest area, 10.44% of NCA, was covered by Boro−Fallow− T. Aman, which was spread out over 32 upazilas. The lowest crop diversity index (CDI) was recorded 0.221 in Agailjhara of Barisal district followed by 0.598 in Bhandaria of Pirojpur. The highest value of CDI was observed 0.972 in Charfasson followed by 0.968 in Tazumuddin of Bhola. The range of cropping intensity values was observed 107-249%. The maximum value was for Bhola sadar and minimum for Agailjhara of Barisal. The overall CDI of Barisal region was calculated 0.968 and the grand mean for cropping intensity at regional level was 204%. Bangladesh Rice j. 2017, 21(2): 57-72